Choctaw as a Window into the Clitic/Agreement Split1. (10th October 2018) - Tyler, Matthew
Abstract: The Choctaw verb hosts argument‐referencing morphemes that could plausibly be analyzed as φ‐agreement affixes or argument‐doubling clitics. I argue that (almost) all the morphemes in question are clitics, on the basis of several state‐of‐the‐art tests. The bulk of the argumentation comes from two of the morphemes' properties in particular: firstly, they participate in clitic‐climbing alternations, and secondly, they are able to license the extrinsic plural marker oklah, an element with the syntactic licensing conditions typical of floating quantifiers. Following much work proposing that clitics have the syntactic status of determiner heads in an A‐movement chain with their DP associate, I show that the properties just outlined follow straightforwardly from a clitic analysis, but would not be predicted under a φ‐agreement analysis.